2015
DOI: 10.7763/ijtef.2015.v6.450
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Development and Economic Growth: Evidences from Egypt

Abstract: Abstract-This study investigates the causal relationship between stock market development and economic growth in Egypt. To achieve this objective, unit root tests were conducted for time series data for the period of 2002 to 2013 in their levels and their first differences according to Dickey-Fuller. Johansen co-integration analysis was conducted to examine whether the variables are co-integrated of the same order. Vector autoregression estimates (VAR) was chosen to test the long-run relationship between stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In the case of Egypt, Badr (2015) found no causal relationship between stock market development and economic growth.…”
Section: Abbs Financial Marketsmentioning
confidence: 90%
“…In the case of Egypt, Badr (2015) found no causal relationship between stock market development and economic growth.…”
Section: Abbs Financial Marketsmentioning
confidence: 90%
“…Luintel and Khan (1999), Magid (2007), Hongbin (2007), and Dawson (2008) were among the studies whose results synchronized with the findings of category (iv) and were among the results of some of the studies (that supported the existence of bi-directional or feedback causality between SMD and EG). Badr (2015) investigated the relationship between SMD and Egyptian EG using the Vector Auto-Regressive Granger causality test and discovered that SMD alone cannot promote EG. The study included a control variable (foreign direct investment) in the econometric model and established a causal relationship between SMD and EG.…”
Section: Literature Review Stock Market Performance and Economic Growthmentioning
confidence: 99%
“…While two of indices exhibited positive impact, the two others were inversely related to economic growth. Accordingly, Bader (2015) concluded that there is no causal relationship between stock market development and economic growth in Egypt. In like manner, Khetsi and Mongale (2015) found a positive relationship between capital market development and economic growth in South Africa.…”
Section: Review Of Related and Empirical Literaturementioning
confidence: 99%